Formulation and Characterization of Herbal Hair Oil for Prevention of Grey Hair - P Ahirrao, Sapana; Y Shirsath, Suchita; V. Patil, Sarika; P. Chavan, Devyani; Baviskar, Anagha V.; V. Algat, Sarika; V. Gaidhani, Vaidehi; L. Nikam, Preetam (Journal of Neonatal Surgery, 2025)
Oxidative stress is one of the major reasons of production of free radicals is discovered to be the most significant of these reasons for grey hair. Oxidative stress also accelerates the apoptosis of melanocytes found in the hair bulb, which results in a loss of regeneration ability as well as the conversion of amelanogenic melanocytes into melanogenic ones.So, the main focus of this study to find out natural alternative which is rich in minerals like iron, folic acid, and vitamins like A, C, and E with antioxidant property which is used to prevent the grey hairs. The plants used for this study is Murraya koenigii (Curry leaf, family rutaceae), Trigonellafoenum-graecum (fenugreek, family: Fabaceae) Indigoferatinctoria (nilli. Family: Fabaceae). Hydroalcoholic extract of M. Koenigii and powder sample of fenugreek and indigo showed the presence of alkaloid, flavonoid. tannins in their phytochemical screening. Oil based herbal formulation was prepared using finely powdered samples of curry leaves, fenugreek and nilli using pure coconut oil. Resulting formulation was evaluated by various parameters like pH, organoleptic properties (Color, Odor), acid value, saponification value. All these plants consist of essential nutrients such as flavonoid, tannins, vitamin, terpenoids and many essential oils helps to maintain normal function hair and prevention of premature hair growth.